24959
Answered

Westonci.ca offers fast, accurate answers to your questions. Join our community and get the insights you need now. Explore our Q&A platform to find in-depth answers from a wide range of experts in different fields. Discover detailed answers to your questions from a wide network of experts on our comprehensive Q&A platform.

2x-y=7
3x-2y=10
Solve with substitution show steps please.


Sagot :

9514 1404 393

Answer:

  (x, y) = (4, 1)

Step-by-step explanation:

Step 1. Look for an equation that has a coefficient of 1 or -1 for one of the variables. Here, that is the first equation, which has a y-coefficient of -1.

Step 2. If you found such an equation, solve for the variable.

  y = 2x -7

Step 3. Use that expression for the variable to substitute into the other equation.

  3x -2(2x -7) = 10

Step 4. Solve the resulting equation in the usual way.

  3x -4x +14 = 10 . . . . . eliminate parentheses

  -x +14 = 10 . . . . . . . collect terms

  4 = x  . . . . . . . . . separate variable terms and constant terms. Here, we added x-10 to both sides.

If the variable has a coefficient that is not 1, divide both sides by that coefficient.

Now, you can use this value in the expression for y that we found above.

  y = 2(4) -7 = 1

The solution is (x, y) = (4, 1).